2009
DOI: 10.1097/opx.0b013e318194e962
|View full text |Cite
|
Sign up to set email alerts
|

Blinking and Tear Break-Up During Four Visual Tasks

Abstract: Reduced and incomplete blinking along with increased tear film break-up during normal visual tasks may explain the increased level of ocular discomfort symptoms reported at the end of the day, particularly in dry eye patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(183 citation statements)
references
References 37 publications
11
157
0
3
Order By: Relevance
“…15 We and others have shown that dry eye patients often repeatedly display TBU during tasks such as computer use, during which the blink rate is known to slow markedly. 45,46 Thus, in patients with extensive and rapidly developing TBU (as in subjects 3 and 4), it appears likely that inadequate blinking could lead to discomfort and repeated stimulation of surface nociceptors over the day. This may explain, in part, the origin of dry eye symptoms because repeated nociceptor stimulation is associated with increased inflammation and hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…15 We and others have shown that dry eye patients often repeatedly display TBU during tasks such as computer use, during which the blink rate is known to slow markedly. 45,46 Thus, in patients with extensive and rapidly developing TBU (as in subjects 3 and 4), it appears likely that inadequate blinking could lead to discomfort and repeated stimulation of surface nociceptors over the day. This may explain, in part, the origin of dry eye symptoms because repeated nociceptor stimulation is associated with increased inflammation and hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Malaysia was conducted on 795 college students aged 18-25 years. They experienced headaches along with eyestrain, with 89.9% of the students surveyed feeling any type of symptoms of CVS [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the one hand, increasing cognitive demands have been reported to result in a reduction in SBR, both during computer tasks [7][8][9][10][11] and other activities such as reading or watching a video story. 4,5 On the other hand, blinks tend to be associated with large gaze shifts, rather than saccades of smaller amplitude such as those involved in reading, 20,21 partially contributing to sustaining visual stability through momentary suppression of visual input, 16,17 which is particularly relevant for large gaze shifts, were saccadic suppression is less effective.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, a similar reduction in blinking frequency with increasing task complexity has been evidenced in relation to computer use, a field in which spontaneous blinking has been extensively studied in order to understand and alleviate the symptomatology associated with the traditionally known as ''computer vision syndrome''. [7][8][9][10][11] Interestingly, from a different perspective, the increased blink rate observed in studies investigating behavioral indicators of fatigue and drowsiness has been related to a cessation of the attention-driven inhibitor of blinks.…”
Section: Q1mentioning
confidence: 99%